2021
DOI: 10.51936/tip.58.3.1089-1116
|View full text |Cite
|
Sign up to set email alerts
|

The Prospects of Food Sovereignty in the Former Yugoslav Republics

Abstract: Abstract. The neoliberal approach taken to the transition from socialism to capitalism in the six former Yugoslav republics has revealed its weaknesses in all spheres of economic activities, including food production. These countries have lost sovereignty with respect to regulating important national policy areas like food trade and production. Liberalisation of the food trade has adversely affected national economies by destroying many small-scale farmers and food producers. Corporate supermarkets have been t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…At the end, the events turned violent and reached the point of "no return", when ethnic, religious and/or cultural identities prevailed over the Yugoslav idea. Last, but not least, there have been several examples of pragmatic but solid coexistence (Djordjević & Zupančіč, 2024;Hayden, 2002;-although various longitudinal studies have confirmed a degree of ethnic distance between the groups in the former Yugoslavia (Rašković & Vuchkovski, 2016). Despite intensive peacebuilding efforts in the region, relations between ethnic groups remain highly polarised and conflictual to date (Ajduković & Čorkalo Biruški, 2004;Čorkalo Biruški & Ajduković, 2012;Funk & Berry, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…At the end, the events turned violent and reached the point of "no return", when ethnic, religious and/or cultural identities prevailed over the Yugoslav idea. Last, but not least, there have been several examples of pragmatic but solid coexistence (Djordjević & Zupančіč, 2024;Hayden, 2002;-although various longitudinal studies have confirmed a degree of ethnic distance between the groups in the former Yugoslavia (Rašković & Vuchkovski, 2016). Despite intensive peacebuilding efforts in the region, relations between ethnic groups remain highly polarised and conflictual to date (Ajduković & Čorkalo Biruški, 2004;Čorkalo Biruški & Ajduković, 2012;Funk & Berry, 2020).…”
Section: Introductionmentioning
confidence: 99%